ANALISIS KECELAKAAN KERJA DI BAGIAN PRODUKSI PT. YYY LAMPUNG PLANT DENGAN METODE FMEA DAN FTA - Muhammad Indra Jaya; Susanti Sundari; Suharto (Fakultas Teknik Universitas Tulang Bawang Lampung, 2021)
This research discusses the Analysis of Work Accidents with FMEA and FTA Methods in the Production Section of PT. YYY Lampung Plant. The purpose of this study is to determine the risk factors that cause work accidents, types of work accidents, work accident rates, and the root causes of work accidents in the production department. This research is a quantitative descriptive study with data analysis using FMEA and FTA methods. The data collection method used primary data in the form of work accident data and secondary data in the form of questionnaires to 50 employees. The results showed that the risk factors for work accidents exist in 5 production process activities, namely in the process of selecting raw materials, cutting, weighing, product formation, and finishing. The types of work accidents that often occur are pinched, crushed, sliced, and hit the body, while the highest accident rate with an RPN value of 350.6 is pinched in the finishing process. The results of this RPN value indicate that the number of work accidents is a very high number (> 200). And the root cause of work accidents based on Fault Tree Analysis on work accidents in the form of being squeezed with a RPN value of 350.6 caused by lack of concentration, employees not feeling well, sleepy workers, and limited (narrow) work space. Based on these data, it can be concluded that the level of work accidents should receive special attention.